Attentional Switching in Humans and Flies: Rivalry in Large and Miniature Brains - Miller, Steven M.; Ngo, Trung T.; van Swinderen, Bruno (Frontiers in Human Neuroscience, 2012)
Human perception, and consequently behaviour, is driven by attention dynamics. In the special case of rivalry, where attention alternates between competing percepts, such dynamics can be measured and their determinants investigated. A recent study in the fruit fly, Drosophila melanogaster, now shows that the origins of attentional rivalry may be quite ancient. Furthermore, individual variation exists in the rate of attentional rivalry in both humans and flies, and in humans this is under substantial genetic influence. In the pathophysiological realm, slowing of rivalry rate is associated with the heritable psychiatric condition, bipolar disorder. Fly rivalry may therefore prove a powerful model to examine genetic and molecular influences on rivalry rate, and may even shed light on human cognitive and behavioural dysfunction.